Virtual classes and their effect on the physical and mental state of university students - Arias, Paul Arias (2021)
The physical pain caused by poor ergonomics in virtual classrooms in times of epidemic has made it difficult for some students. The following research carried out on the first and second grade ESPE students shows that bad eating habits and too little physical exercise are not because we are not aware of this, but because of the simple fact that we do not have good habits, if we practice good habits our body would reward us. Good habits are generated in being better every day, that is, if you want to have a full life without any discomfort or discomfort due to any symptoms, we must take care of our body, in this research we will see a series of recommendations that will help avoid these possible problems and that The best cure is prevention, based on exercises, a good diet and meditation with proven results. By improving our body free of discomfort, we will also have psychological rewards since we will feel good about ourselves, our body will become lighter, we will have more energy, we will perform better in college, its side effects will benefit us in the vast majority, however research shows us that for For that to happen, we lack great changes in discipline and perseverance in an average student.